(3GdEJLGgGJ GdMOjKI aj EOGQI GdehGQO GdHTQjI (B/s - (3GdYJjHj, eMeO RhjOs ((3YeGf(B: s (3eDSSI GdhQGb(B, s, 2010)
(3eaghe hCgejI GdehGQO GdHTQjI h GdGJLgGJ GdMOjKI h GdJfXje GdGOGQj dgG , GdGfXeI h GddhGFM GdJj dgGYdGbI HGOGQI GdehGQO GdHTQjI h GdJMOjGJ GdJj JhGLggG , JMdjd h JNWjW Gdbhi GdYGedI , GdGSJbWGH GdhXjaj h GdebGHdGJ h GdGNJHGQGJ GdhXjajI , GdGSJbWGH h GdGNJjGQ GdhXjaj HGdeedcI , Jbhje GdCOGA GdhXjaj eY hLhO JeGQjf h JWHjbGJ (B.s
(3eQGLY U(B.225s
Keywords: (3EOGQI GdCaQGOs; (3Gdbhi GdYGedIs; (3GdehGQO GdHTQjIs; (3GdehGQO GdHTQjI `` EOGQIs